1996
DOI: 10.1007/bf00020491
|View full text |Cite
|
Sign up to set email alerts
|

Application of differential display RT-PCR to the analysis of gene expression in a plant-fungus interaction

Abstract: Establishment of a plant-pathogen interaction involves differential gene expression in both organisms. In order to isolate Botrytis cinerea genes whose expression is induced during its interaction with tomato, a comparative analysis of the expression pattern of the fungus in planta with its expression pattern during in vitro culture was performed by differential display of mRNA (DDRT-PCR). Discrimination of fungal genes induced in planta from plant defense genes induced in response to the pathogen was attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
18

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 32 publications
(35 reference statements)
1
31
0
18
Order By: Relevance
“…Our results are partially in agreement with those of Benito et al [10], who studied the differential display expression in tomato plants induced by Botrytis cinerea. They also studied the different plant genes induced by fungal infection, through different patho-genes.…”
Section: Phytophthora(3)supporting
confidence: 93%
See 1 more Smart Citation
“…Our results are partially in agreement with those of Benito et al [10], who studied the differential display expression in tomato plants induced by Botrytis cinerea. They also studied the different plant genes induced by fungal infection, through different patho-genes.…”
Section: Phytophthora(3)supporting
confidence: 93%
“…The trial was conducted twice and the experiment was arranged in a completely randomized block design. After transplanting, samples from treatments (C, RB, RT, FB and FT) were taken at different times (2,4,6,8, and 24 h), to detect the induced defense genes using differential display technique and real-time PCR [10]. Three plants of each treatment were carefully harvested (Three weeks after inoculation with the pathogen), washed under running water to remove soil particles, and evaluated for the following growth parameters: shoot fresh and dry weights, and root fresh and dry weights.…”
Section: Effect Of B Subtilis and T Viride Against F Oxysporum Andmentioning
confidence: 99%
“…Our yield of 0.4 differentially expressed cDNAs per primer combination compares favorably to other studies that have used differential display to analyze plantfungus interactions. In these cases, yields have ranged from 0.08 to 0.31 cDNAs per tested primer combination (9,50,55). Our protocol of replicating each display three or four times before candidate bands were isolated may have contributed to our relatively high confirmation rate.…”
Section: Discussionmentioning
confidence: 99%
“…A cDNA product homologous to chitinase was found to be induced in a plant root after infection with the fungus Azorhizobium caulinodans ORS571 (40). Benito et al identified differentially expressed transcripts from both the fungal pathogen Botrytis cinerea and its host, the tomato, that were induced during the plant-fungus interaction (6). Of course, it is important to confirm the source of the DNA.…”
Section: Biodefensementioning
confidence: 99%
“…Of course, it is important to confirm the source of the DNA. Benito et al discriminated induced B. cinerea genes from plant defense genes by comparing expression patterns from healthy tomatoes and tomatoes infected with two nonrelated pathogens (6). The initial interactions between host and pathogen have also been studied in normal symbiotic organisms, e.g., mycorrhizial fungi (69,89).…”
Section: Biodefensementioning
confidence: 99%